2012
DOI: 10.3892/etm.2012.459
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of rhein in combination with ampicillin or oxacillin against methicillin-resistant Staphylococcus aureus

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) is a bacterium responsible for a number of infections in humans that are difficult to treat, and as a result, is a substantial contributor to morbidity and mortality. In the present study, in search of natural products capable of inhibiting this multidrug-resistant bacterium, we investigated the antimicrobial activity of rhein isolated from Rheum palmatum L. (Polygonaceae) against 16 different strains of the bacterium. New antimicrobial activity was found usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 12 publications
2
21
0
Order By: Relevance
“…The above results are in agreement with previous studies that showed that an anthraquinone-rich extract of another species of rhubarb (Rheum undulatum) exhibited antibacterial activity towards the cariogenic bacterium Streptococcus mutans (Song et al, 2006;Kim et al, 2011). Moreover, synergistic effects of anthraquinones (emodin, rhein) in combination with antibiotics (ampicillin, oxacillin) have been reported for methicillin-resistant Staphylococcus aureus (Joung et al, 2012;Lee et al, 2010). Although we did not investigate the action-mode of rhubarbcontaining Kampos and rhubarb-derived anthroquinones, previous studies suggest that they may act by causing damage to the bacterial cell membrane (Alves et al, 2004) and interfering with DNA replication and transcription (Lu et al, 2011).…”
Section: Discussionsupporting
confidence: 82%
“…The above results are in agreement with previous studies that showed that an anthraquinone-rich extract of another species of rhubarb (Rheum undulatum) exhibited antibacterial activity towards the cariogenic bacterium Streptococcus mutans (Song et al, 2006;Kim et al, 2011). Moreover, synergistic effects of anthraquinones (emodin, rhein) in combination with antibiotics (ampicillin, oxacillin) have been reported for methicillin-resistant Staphylococcus aureus (Joung et al, 2012;Lee et al, 2010). Although we did not investigate the action-mode of rhubarbcontaining Kampos and rhubarb-derived anthroquinones, previous studies suggest that they may act by causing damage to the bacterial cell membrane (Alves et al, 2004) and interfering with DNA replication and transcription (Lu et al, 2011).…”
Section: Discussionsupporting
confidence: 82%
“…Our positive results can also be supported by the fact that the ΣFICs of both combinations observed in this study reached values of ≤0.8 for 84% of all strains tested, which could be assessed as a strong additive effect. This finding is consistent with the results of a previous study demonstrating significantly increased the antibacterial activity of ampicillin and oxacillin enhanced by rhein (active metabolite of diacetyl rhein) against various MRSA clinical isolates as well as MRSA and MSSA standard strains [18]. According to our best knowledge, this is the first report on the synergistic antibacterial effect of diacetyl rhein with oxacillin and the additive effect with tetracycline against S. aureus including its ERSA, MRSA and tetracycline-resistant (TRSA) strains.…”
Section: Resultssupporting
confidence: 82%
“…Because of the closely related structures of diacetyl rhein and rhein and their comparable pharmacological actions [13,16], both have a marked antibacterial effect and potentiate the activity of β-lactams [18,19]; it is also likely that their modes of action could possibly be similar. Since the application of multidrug resistance pump inhibitors INF 271 and MC 207110 has previously been reported to strongly potentiate the antibacterial activity of rhein against the resistance mechanisms of S. aureus by disabling their multidrug resistance pump activity [23], this action can also be expected for diacetyl rhein.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination activities as such against S. aureus remain to be investigated. Indeed, there have been many studies showing the potent antibacterial action of other natural compounds against S. aureus such as thymoquinone [78], rhein [79], emodin [80], silibinin [81], osthol [82], tannic acid [83], and epigallocatechin gallate [84]. These findings warrant the potential use of abovementioned compounds in combination with curcumin against S. aureus .…”
Section: Synergism Of Curcumin With Antibiotics Against S Aureusmentioning
confidence: 99%